Cultivating the Mental Wellness of Faculty, Staff, and Chairs - Jeffrey Reber (Academic Chairpersons Conference Proceedings, 2020)
Presenters and participants will discuss emerging strategies and best practices available to chairs to support the mental health and wellbeing of faculty, staff, and the department chair within the unique context of higher education and given the work-life needs of faculty and staff.
Keywords: mental health; work-life balance; faculty and staff support; academic leadership; ombuds